Artificial Intelligence in Healthcare: A Review - Sharma , Rishabh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Artificial Intelligence (AI) has emerged as a transformative technology in healthcare, promising to revolutionize various aspects of patient care, diagnosis, and treatment. This review provides a comprehensive overview of the applications, benefits, challenges, and future directions of AI in healthcare. The paper discusses the history of AI in healthcare, highlighting key milestones and advancements. It examines the current state of AI in healthcare, focusing on its applications in disease diagnosis and prediction, treatment personalization, medical imaging, and drug discovery. The review also addresses the challenges and limitations of AI in healthcare, including data privacy and security, integration with existing systems, ethical considerations, and patient acceptance. Finally, the paper explores potential advancements in AI healthcare, the integration of AI with other technologies, implications for healthcare professionals, and strategies for addressing challenges and limitations. Overall, the review emphasizes the transformative potential of AI in healthcare and the need for continued research and development to fully realize its benefits.